Bell's dynamic interaction on a reinforced concrete bell tower. (15th March 2019) - Ivorra, Salvador; Foti, Dora; Gallo, Valentina; Vacca, Vitantonio; Bru, David
Highlights: Bell's dynamic interaction. Damage detected generated by bell forces. Methodology to analyze and reduce the dynamic interaction between bells and tower. Durability on concrete reduced by excessive movements generated by bells. Monitoring – Model updating – modeling external forces – analysis of dynamic amplification factor. Abstract: The present study shows a cheap and simple methodology to evaluate the dynamic behavior of a reinforced concrete bell tower built in 1974 made of concrete structural elements and brick masonry walls. The bell swinging vibrations on the tower are evident and they can be visually observed even without the use of any equipment. In this case a possible interaction between the bells' swinging and the tower vibration has been dynamically identified by the methodology here proposed. An experimental campaign was carried out on the bell tower to record the environmental vibrations and the accelerations induced by the movement of the bells during their swinging. In order to develop the methodology here proposed, the main characteristics of the bells have been measured and the time history force generated by each bell during the swing has been evaluated. A numerical model of the tower has been developed and calibrated by the Operational Modal Analysis technique. The model has then been validated utilizing the acceleration time-histories recorded under forced excitations. Dynamic analyses have been carried out on the bell tower and the dynamic amplification factor (DAF) has been determined. From the results it is noticed that the bell tower does not comply with its maximum capacity due to the dynamic interaction with the bells swinging as evidenced by the presence of cracks on the facades of the tower. This paper highlights the dynamic problems that bells can cause to slender bell towers and proposes a simple and cheap solution.